Beyond the straightforward illness narrative - Taher, Menna (AUC Knowledge Fountain, 2020)
While the initial premise of Medical Humanities was to encourage more writings about the illness as lived experience, and to include literary works in the curriculum of medical schools, a second more critical wave has emerged that delves deeper into issues of race, class and gender. As the illness memoir has become a genre, the act of writing about illness is not a feat anymore, and illness narratives now demand more complex questions. Primarily dealing with questions on form and narrative, the thesis tackles major oft-cited works on illness like Tolstoy’s The Death of Ivan Ilyich, Virginia Woolf’s On Being Ill, Susan Sontag’s Illness as Metaphor as well as Audre Lorde’s The Cancer Journals. However, it also analyzes the recently published book, The Undying (2019), by the American poet Anne Boyer. The thesis also briefly taps onto Arabic works like Amal Dunqul’s hospital poetry as well as autobiographies of Radwa Ashour and Ni‘mat al-Buhairy. The Death of Ivan Ilyich by Tolstoy and Anne Boyer’s The Undying, serve as a representation of first and second waves of the medical humanities, respectively. The comparison between the two works through the concepts of “the universal” and “the specific” guides the thesis. While the universal approach is important, it still has its limitations that are highlighted by a text like Boyer’s, which deals with the specific culturally-gendered disease, breast cancer. Audre Lorde’s The Cancer Journals, and Anne Boyer’s The Undying, which blend hybrid genres, tackle breast cancer in a myriad of ways; through the personal, political, philosophical, and aesthetic. While both powerful works, they are also a part of a woman’s life writing tradition, a tradition that now encompasses a numerous works by women writing about their illnesses.